Ultrasensitive dopamine detection with graphene aptasensor multitransistor arrays - Abrantes, Mafalda; Rodrigues, Diana; Domingues, Telma; Nemala, Siva S; Monteiro, Patricia; Borme, Jérôme; Alpuim, P.; Jacinto, Luis (Journal of biomaterials and nanobiotechnology, 2022)
Detecting physiological levels of neurotransmitters in biological samples can advance our understanding of brain disorders and lead to improved diagnostics and therapeutics. However, neurotransmitter sensors for real-world applications must reliably detect low concentrations of target analytes from small volume working samples. Herein, a platform for robust and ultrasensitive detection of dopamine, an essential neurotransmitter that underlies several brain disorders, based on graphene multitransistor arrays (gMTAs) functionalized with a selective DNA aptamer is presented. High-yield scalable methodologies optimized at the wafer level were employed to integrate multiple graphene transistors on small-size chips (4.5 × 4.5 mm). The multiple sensor array configuration permits independent and simultaneous replicate measurements of the same sample that produce robust average data, reducing sources of measurement variability. This procedure allowed sensitive and reproducible dopamine detection in ultra-low concentrations from small volume samples across physiological buffers and high ionic strength complex biological samples. The obtained limit-of-detection was 1 aM (10-18) with dynamic detection ranges spanning 10 orders of magnitude up to 100 µM (10-8), and a 22 mV/decade peak sensitivity in artificial cerebral spinal fluid. Dopamine detection in dopamine-depleted brain homogenates spiked with dopamine was also possible with a LOD of 1 aM, overcoming sensitivity losses typically observed in ion-sensitive sensors in complex biological samples. Furthermore, we show that our gMTAs platform can detect minimal changes in dopamine concentrations in small working volume samples (2 µL) of cerebral spinal fluid samples obtained from a mouse model of Parkinson's Disease. The platform presented in this work can lead the way to graphene-based neurotransmitter sensors suitable for real-world academic and pre-clinical pharmaceutical research as well as clinical diagnosis. This work was funded by: "la Caixa" Banking Foundation under grant agree ment LCF/PR/HR21-00410; national funds, through the Foundation for Science and Technology (FCT)—projects UIDB/50026/2020, UIDP/50026/2020, and UIDB/04650/2020; by FCT project PTDC/MED-NEU/28073/2017 (POCI-01-307 0145-FEDER-028073); by The Branco Weiss fellowship—Society in Science (ETH Zurich); and by FCT Ph.D. fellowships SFRH/BD/14536/2022 (M.A.), SFRH/BD/08181/2020 (T.D.), and PD/BD/127823/2016 (D.R.).